Brand recognition management. Approaches and perspectives. A systematic review from 2012-2022 (LACCEI, 2024)
The objective of this systematic review was to analyze theoretical and empirical studies on how to connect with the customer's mind, achieving a brand positioning with respect to its competitors, thus improving brand recognition and identity. The sources of information are the databases Ebsco, Scopus, Dialnet, ProQuest, Redalyc and Scielo, the criteria for eligibility were: articles with related research subtopics, period of the last 10 years and evaluated by experts therefore, those that did not meet these criteria were excluded. As a result, 50 effective articles were obtained in which brand positioning studies were carried out and branding strategies were applied. The results show that the degree of awareness of brand recognition is high. However, the degree of application is low, due to the fact that companies do not apply branding strategies correctly. Finally, the main focus of brand awareness is to study consumer behavior with the perspective of customer identification with the brand in the companies.